Schistosomicidal Effects of the Essential Oils of Citrus limonia and Citrus reticulata Against Schistosoma mansoni. Issue 1 (29th December 2016) - Martins, Moara H. G.; Fracarolli, Letícia; Vieira, Tatiana M.; Dias, Herbert J.; Cruz, Michele G.; Deus, Cássia C. H.; Nicolella, Heloiza D.; Stefani, Ricardo; Rodrigues, Vanderlei; Tavares, Denise C.; Magalhães, Lizandra G.; Crotti, Antônio E. M.
Abstract : We report the in vitro schistosomicidal effects of the essential oil obtained from Citrus limonia leaves (CL‐EO) and C. reticulata fruit peels (CR‐EO), cultivated in Brazil, against Schistosoma mansoni worms. Limonene (29.9%), β ‐pinene (12.0%), sabinene (9.0%), citronellal (9.0%), and citronellol (5.8%) are the major constituents of CL‐EO; limonene (26.5%), γ ‐terpinene (17.2%), linalool (11.1%), octanal (8.0%), myrcene (6.2%), and capraldehyde (3.9%) predominate in CR‐EO. CL‐EO displayed moderate lethal concentration 50% ( LC 50 ) of 81.7 and 38.9 μg/ml against male and female worms at 24 and 72 h, respectively. At concentrations of 25 and 100 μg/ml, CL‐EO separated between 50 and 75% of the coupled worm pairs during the evaluated period. CR‐EO presented moderate LC 50 of 81.7 μg/ml against male and female worms at 24 and 72 h. However, this oil separated coupled worm pairs more effectively than CL‐EO and displayed lower cytotoxicity to GM07492‐A cells ( IC 50 = 987.7 ± 88.9 μg/ml) as compared to CL‐EO ( IC 50 = 187.8 ± 2.9 μg/ml). The enantiomers (+)‐( R )‐limonene and (−)‐( S )‐limonene did not affect S. mansoni adult worm pairs significantly. Taken together, these data indicate that CL‐EO and CR‐EO exhibit moderate in vitro schistosomicidal activity against adult S. mansoni worms. Abstract :